The analysis of international trade impact on economic development. (Journal of Economic Research & Business Administration, 2015)
The barter of goods or services among different peoples is an age-old practice, probably as old as human history. International trade, however, refers specifi cally to an exchange between members of different nations, and accounts and explanations of such trade begin only with the rise of the modern nation-state at the close of the European Middle Ages. As political thinkers and philosophers began to examine the nature and function of the nation, trade with other countries became a particular topic of their inquiry. Much of the modern history of international relations concerns efforts to promote freer trade between nations. This article provides a historical overview of the structure of international trade, the leading institutions and the production analysis of Kazakhstan for 20 years using the real GDP curve.
Keywords: international trade; international trade model; economic development; real GDP of Kazakhstan; export; import